2022
DOI: 10.1155/2022/8528938
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Immunomodulatory Mechanism of Acupuncture in the Treatment of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) is a chronic inflammatory disease with a high prevalence and canceration rate. The immune disorder is one of the recognized mechanisms. Acupuncture is widely used to treat patients with IBD. In recent years, an increasing number of studies have proven the effectiveness of acupuncture in the treatment of IBD, and some progress has been made in the mechanism. In this paper, we reviewed the studies related to acupuncture for IBD and focused on the immunomodulatory mechanism. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Therefore, it is very important to assess whether acupuncture can alleviate NAFLD by mediating autophagy and apoptosis through related pathways. In addition, new evidence also suggests that NAFLD is closely related to intestinal flora, and acupuncture has been proved to be involved in the treatment of various diseases, including nervous system diseases, endocrine diseases, and digestive system diseases, by regulating intestinal flora [51][52][53]. The correlation between acupuncture and intestinal flora is also worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important to assess whether acupuncture can alleviate NAFLD by mediating autophagy and apoptosis through related pathways. In addition, new evidence also suggests that NAFLD is closely related to intestinal flora, and acupuncture has been proved to be involved in the treatment of various diseases, including nervous system diseases, endocrine diseases, and digestive system diseases, by regulating intestinal flora [51][52][53]. The correlation between acupuncture and intestinal flora is also worth exploring.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the body is stimulated, initial CD4+ T cells substantially differentiate into Th17 immune cells and disrupt the balance, which may lead to abnormal immune responses and intestinal inflammation. Studies showed that EA at Tianshu (ST25) and Zusanli (ST36) has the ability to restore the normal ratio of Treg and Th17 cells in spleen lymphocytes of UC mice ( Sun et al, 2017 ), which helps to improve intestinal inflammatory response ( Liu Z. et al, 2022 ). Furthermore, EA could also relieve intestinal mucosal inflammation and autoimmune diseases by regulating marker transcription factors of immune cells such as RORyt and Foxp, as well as their metabolic pathways ( Liu Z. et al, 2022 ).…”
Section: Can Acupuncture and Moxibustion Therapy Improves Cognitive I...mentioning
confidence: 99%
“…Studies also showed that EA at ST36, ST37, ST39, and other acupoints could attenuate inflammation by inhibiting the activity of myeloperoxidase (MPO), which is produced by granulocytes and can activate neutrophils ( Yang et al, 2020 ). Wu et al demonstrated that acupuncture therapy could suppress oxidative stress in UC rats by regulating related markers such as SOD, CAT, and MDA, which are involved in the pathogenesis and progression of IBD ( Liu Z. et al, 2022 ).…”
Section: Can Acupuncture and Moxibustion Therapy Improves Cognitive I...mentioning
confidence: 99%
“…It decreased serum antibodies and nitric oxide and also affected the levels of inflammatory signaling molecules (such as ERK, NF-κB, AP-1, p38, etc.) ( 69 ). This modulation of T cell subsets and their associated inflammatory response factors was considered an important cellular immune mechanism for acupuncture in the treatment of allergic diseases and nonspecific inflammatory diseases ( 70 73 ).…”
Section: Acupuncture In Regulating Immune Microenvironmentmentioning
confidence: 99%